Considerations on the Life Cycle of Laminosioptes cysticola (Vizioli, 1870) Based on a Natural Infestation in Two Laying Hens - Iolanda Moretta; Simona Principato; Giuseppe Giglia; Elvio Lepri; Mario Antonello Principato (Animals, 2025)
Laminosioptes cysticola (Vizioli, 1870), a tissue-dwelling mite responsible for nodular acariasis in birds, was identified from two hens reared in a rural backyard flock in Umbria, Italy. Adult mites were found in the subcutaneous tissue and on the serosal surface of various internal organs. Larval and first- and second-stage nymphal forms were observed beneath the skin and near the trachea and esophageal serosa. By comparing the existing literature with that reported in the present study, we propose a hypothetical reconstruction of the parasite’s life cycle. It is postulated that the entry of L. cysticola occurs through the cervical skin, where adults mate and larviparous females give birth to larvae. These larvae migrate into the loose connective tissues surrounding the trachea and esophagus, where they develop into nymphs. The immature forms then progress along the esophagus and trachea to reach the thoracic and abdominal cavities, colonizing the serosal surfaces of visceral organs. It remains unclear whether, or how, the mites return to the subcutaneous tissues to complete their maturation. Senescent specimens degenerate within the subcutis, where they are encased by a granulomatous inflammatory reaction that leads to the formation of characteristic calcified nodules.